1996
DOI: 10.1200/jco.1996.14.9.2495
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of high-dose thiotepa and etoposide with autologous bone marrow rescue in children and young adults with recurrent CNS tumors. The Children's Cancer Group.

Abstract: The combination of high-dose thiotepa and etoposide has activity against a variety of recurrent childhood brain tumors. These results merit further evaluation in children and young adults with both recurrent and newly diagnosed high-grade brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(118 citation statements)
references
References 15 publications
2
114
0
2
Order By: Relevance
“…However, despite a high response rate, responses at time of relapse are often transient. This has led to the assessment of high-dose therapy for responding patients using various regimens (Kalifa et al, 1992;Finlay et al, 1996;Mahoney et al, 1996). The most promising results concern high-dose chemotherapy in relapsing infants previously non-irradiated (Dupuis-Girod et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite a high response rate, responses at time of relapse are often transient. This has led to the assessment of high-dose therapy for responding patients using various regimens (Kalifa et al, 1992;Finlay et al, 1996;Mahoney et al, 1996). The most promising results concern high-dose chemotherapy in relapsing infants previously non-irradiated (Dupuis-Girod et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The most promising results concern high-dose chemotherapy in relapsing infants previously non-irradiated (Dupuis-Girod et al, 1996). Encouraging preliminary survival data have been reported by Finlay (1996) with the use of high-dose chemotherapy in patients with recurrent medulloblastoma. In this experience, children with minimal tumour burden are the ones who benefit from myeloablative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…9 Promising results with HDCT/ASCT prompted us to use this form of therapy for young adults with recurrent medulloblastoma, who were otherwise healthy and had no possibility of cure with conventional dose therapy. [10][11][12][13][14][15] Here, we report the outcomes of six adults who underwent HDCT (cyclophosphamide, carboplatin, thiotepa, etoposide) with ASCT for medulloblastoma relapse. Table 1 lists the clinical profile of patients 1-6.…”
mentioning
confidence: 99%
“…11 Etoposide has exhibited a good level of penetration into brain parenchyma as well, 12 and both of these agents have demonstrated good activity against recurrent brain tumors at conventional doses. [13][14][15] Finlay et al 20 treated 45 patients with high doses of etoposide (1500 mg/m 2 ) and thiotepa (900 mg/m 2 ) followed by autologous stem cell rescue; those investigators obtained a 23% CR ϩ PR rate in heavily pretreated patients and a 16% toxicity-related death rate. Bouffet et al 21 treated 22 patients with recurrent or newly diagnosed high-grade glioma and reported a 29% response rate (1 CR and 3 PRs) along with an OS rate no better than what had been achieved using conventional treatment.…”
Section: Discussionmentioning
confidence: 99%